Ankle and foot deformities and malformations in proximal femoral focal deficiency - Chomiak, Jiri; Frydrychova, Monika; Ošťádal, Martin; Dungl, Pavel (Journal of children's orthopaedics, 2025)
PURPOSE: To describe foot abnormalities in proximal femoral focal deficiency and their correlation to the severity. METHODS: Eighty-nine extremities in 87 patients were evaluated between 1996 and 2020 clinically and radiologically. Fibula length, ankle shape, tarsal coalitions, and the number of foot rays were recorded. Extremities with proximal femoral focal deficiency were classified according to Pappas and divided into severe (classes II and V), medium severe (classes III and IV), and mild groups (classes VII, VIII, and IX). RESULTS: The fibula was short in 89% and absent in 11% of cases. An absent fibula occurred mostly in severe class III and only in 4% of mild grades (statistically significant, p = 0.004). The valgus ankle joint prevailed in 82% of cases. Spherical ankle joints (18% of cases) were associated in all cases with a tarsal coalition. Tarsal coalitions occurred in 14.6% and were present in all classes except class IV. Five ray feet were found in 83% of cases, four ray feet were found in 16%, and three ray feet in one extremity. Reduction in the number of foot rays occurred more commonly in association with fibular aplasia (30%). CONCLUSIONS: Abnormalities of the fibula and ankle joint represent a constant part of proximal femoral focal deficiency, whereas tarsal coalition and a reduction of foot rays do not. The severity of foot abnormalities does not correlate to the severity of proximal femoral focal deficiency but does with fibular aplasia.
Keywords: Foot; subtalar synostosis; lateral ray deficiency; proximal femoral focal deficiency; fibula deficiency